Penyakit Jantung Rematik pada Anak - Zafira Uswatun Hasanah; Elvi Suryati (Medula, 2020)
Acute rheumatic fever (DRA) is an inflammatory condition that can affect various organs and systems such as the heart, joints, central nervous system and subcutaneous tissue due to group A β hemolytic Streptococcal infection. Rheumatic heart disease (CHR) occurs when cross reactions between carbohydrate cell walls bacteria with heart valve tissue causing chronic damage to the heart valves. The prevalence of PJR reaches 33 million cases and causes about 270,000 deaths each year. A 15 year old girl came for treatment complaining that she often felt weak since 3 months ago, especially every moderate-heavy activity and recovered when resting. Limp is exacerbated during menstruation. The patient also experienced shortness of breath during moderate to heavy activity. The patient had a history of cough and fever and a wound on the left leg. On physical examination of the patient, it was found that the general condition looked moderate, mental compost, pulse 112 times / minute, blood pressure 110/80 mmHg, breath rate 20 times / minute, temperature 37.5 degrees Celsius and body weight 52 kg. On examination of the head, it was found that the tonsils were enlarged with detritus. And on the chest examination found a systolic ejection murmur. The results of investigations showed positive ASTO immunoserology. Chest X-ray shows the heart is not enlarged. The patient was diagnosed with rheumatic heart disease. Patients are advised to reduce strenuous activities. Patients were given benzathine penicillin 1.2 million / IU IM once a day, prednisone 2mg / kgBW / day 2-6 mg, and captopril 2x 12.5 mg.